The evolving role of avotermin in scar prevention. (April 2011) - Nauta, Allison; Gurtner, Geoffrey C; Longaker, Michael T
Evaluation of: Bush J, Duncan JA, Bond JS et al. Scar-improving efficacy of avotermin administered into the wound margins of skin incisions evaluated by a randomized, double-blind, placebo-controlled, Phase II clinical trial. Plast. Reconstr. Surg. 126(5), 1604––1615 (2010). Scar formation is a medical problem that affects a diverse population of patients, at times leading to devastating physical and psychological consequences. In contrast to adult skin, early gestational fetal skin heals without scar formation. This discovery has led to a large field of research related to defining the factors responsible for scarless wound healing. The TGF-ββ superfamily has been a major focus for the field of regenerative medicine, as its three mammalian isoforms exhibit varying degrees of activity between fetal and adult skin. Avotermin is a novel human recombinant TGF-ββ3 protein that has been studied both in vitro and in vivo for its antiscarring properties. This article evaluates a recently published Phase II clinical trial focused on the role of avotermin as a prophylactically administered, scar-reducing biologic agent for the treatment of human incisional wounds.